enytavadb@gmail.com - Jerizal Petrus; Stenlly J _Patalatu (Cakrawala: Jurnal Pendidikan, 2020)
The Effect of Bullying Against Student Confidence in elementary school in the Middle Tobelo District of North Halmahera Regency". The purpose of this study was to determine: The effect of bullying on student confidence in elementary schools in Central Tobelo District. The method used in this study is a quantitative method with a population of all students in elementary schools in North Tobelo Tengah District of North Halmahera with a sample of 100 students. Data collection using bullying scale and confidence and analyzed using simple regression analysis through the application of SPSS version 20. The results of this study indicate that bullying has a negative and significant effect on self confidence seen from the t test where t count = -5,570 <t.table = 1,984 while to determine the size of the contribution can be seen in the Determination Coefficient Test, where the contribution of bullying variables to confidence is 24% and other factors by 76%. Thus the results of the hypothesis test that H0 is rejected and Ha is accepted, this test statistically proves that bullying can affect student confidence in elementary schools throughout Central Tobelo District.